Peran Strategis Indonesia di Samudra Hindia dalam Dinamika Geopolitik Regional - Khumar Shubham; Risa Amalia Kurniawati; Sri Ratna Sari; Rizky Arfiyanto; Bambang Syaeful Hadi; Gunawan Santoso (Jurnal Pendidikan Transformatif (JPT), 2024)
The Indian Ocean plays a strategic role in regional geopolitics, particularly as a global trade route and a rich source of natural resources. Indonesia, with its strategic geographical position, plays a vital role in maintaining regional stability. This article examines Indonesia's role in maritime security, regional cooperation through forums such as the Indian Ocean Rim Association (IORA), and the challenges faced, including transnational threats such as piracy, human trafficking, and environmental degradation. Through maritime diplomacy and strengthening national capacity, Indonesia seeks to enhance its influence as a maritime nation. This study employs a descriptive qualitative method by analyzing policy literature related to geopolitics and maritime security. The findings highlight the importance of regional collaboration in addressing challenges in the Indian Ocean and Indonesia's strategic position in the region's geopolitical dynamics.